Double-tap to disordered eating: the effect of social media influencers on Palestinian female university students: a mixed-method study - Anabtawi, Ola; Irshaid, Alma; Ayoub, Haya; Saleh, Faisal (Frontiers in Communication, 2025)
IntroductionThe goal of this study is to explore how using social media and content from influencers affects disordered eating symptoms among female university students.MethodsThis was done using a combination of a purpose-built online survey (with 1,121 participants) and a qualitative content analysis of the social media influencers in beauty, health, and lifestyle that the participants follow the most.ResultsThe findings revealed that 65.3% of the sample spends more than three hours per day on social media networking sites; additionally, the majority reported that they use social media as a source of reliable information, and half reported that they are influenced by social media influencers. The EDE-Q tool yielded higher scores in the weight and shape concern sub-categories, with mean scores of 1.99 (1.51) and 1.98 (1.62), respectively. In terms of content analysis, four social media accounts with a total of 218 posts were examined, yielding two main themes: photography to emphasize ideal bodies and beauty and happiness.ConclusionThese findings emphasize the impact of social media on the studied sample and highlight the importance of implementing tailored policies to mitigate its negative effects on this group’s dietary behavior.